PENGARUH MEKANISME CORPORATE GOVERNANCE DAN LEVERAGE TERHADAP MANAJEMEN LABA, NILAI PEMEGANG SAHAM DAN COST OF EQUITY CAPITAL PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Yuniarsih, Nia (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2012)
This study was aimed to analyze the effect of managerial ownershipsconcentration institutional, ownerships concentration and leverage towardsearnings management, shareholders value and cost of equity capital. This studywas based on agency theory and economic consequences.This study was performed using field research. Data were collected fromThe Indonesian Capital Market Directory (ICMD). The population in this study is142 firms which are listed at the Jakarta Stock Exchange from 2009-2010 andderived using some criteria. This study use Path Analysis technique.The result showed that earnings management was negatively affected bymanagerial ownerships concentration and institutional ownerships concentrationand positively affected by leverage. Shareholders value was negatively affectedmanagerial ownerships concentration, and positively affected by institutionalownerships concenteration, leverage and earnings management. Cost of equitycapital was positively affected by managerial ownerships concentration,institutional ownerships concentration, earnings management, and shareholdersvalue.The findings might be of interest to investors and creditors to makeinvestment and credit decision. The study contributed to the literature in that hasshown that earnings management is driven by shareholders value increasingrather than motive opportunistic management. Institutional ownershipsconcentration was positively reaction by capital market, so that evidence of themwerenât expropriation on minority shareholderâs and capital market.The result of this study attractive to investors and creditors in makinginvestment decisions. This study contributes to shareholders value is affected byearnings management is not purely due to opportunistic behavior.